Chennai, India. (February 2015) - Krishnamurthy, Rashmi; Desouza, Kevin C.
Highlights: In this profile, we feature the city of Chennai, capital of Tamil Nadu, India. In recent decades, large industrial facilities have proliferated in Chennai and its suburbs – resulting in large-scale population growth. We trace Chennai's urban history from a social, economic, political, and environmental prospective to highlight current and future challenges facing the city. We argue that the city is well poised to leverage emerging smart city technologies. However, to effectively implement smart city technologies, city administrators need to undertake several measures. Abstract: Cities around the world are experiencing tremendous population growth, and this is especially true in the developing world. In this profile, we feature the city of Chennai, the capital of Tamil Nadu, India. Chennai is the largest industrial commercial center in South India; it is often referred as the "Detroit of India" and the "Gateway to South India." In recent decades, large industrial facilities have been established in Chennai and its suburbs—resulting in large-scale population growth. However, this explosive growth has strained the urban infrastructure of this prominent city. In this profile, we provide an overview of Chennai's urban history from social, economic, political, and environmental perspectives. We highlight the current and future challenges faced by the city, and we argue that it is well poised to leverage emerging smart city technologies. However, to effectively implement these technologies, city administrators need to undertake several measures; for example, a database capturing all dimensions of the city must be developed. By clearly delineating the urban planning and policy efforts to the present and offering a way forward, this paper contributes to the growing literature on smart cities and the unique urban challenges faced by cities in the developing world.